Environmental correlates of objectively measured physical activity and sedentary behavior in after-school recreation sessions - Rosenkranz, Richard R.; Welk, Greg J.; Dzewaltowski, David A. (My University, 2011)
Background: Active recreation sessions taking place within after-school programs (ASP) present an opportunity for attending children to attain part of the recommended 60 minutes of daily moderate-to-vigorous physical activity (MVPA). This cross-sectional study’s purpose was to assess relationships between microlevel ASP environmental characteristics and physical activity and sedentary behavior (SED). Methods: During 161 ASP active recreation sessions, 240 children from 7 schools wore Actigraph GT1M accelerometers and were observed up to 6 times per year, over 3 years. To provide microlevel environmental data, trained observers recorded session times, location, duration, organization, equipment, and number of children and staff. Unadjusted bivariate correlations and multivariable regression analyses were used to assess the influence of microlevel environmental variables on MVPA and SED, with regression models controlling for relevant covariates. Results: Across all ASP active recreation sessions, children spent 39 ± 15% in MVPA and 16 ± 11% in SED. Session location, boy-to-girl ratio, and duration were significantly related to MVPA in the regression model. For SED, location and duration were significant influences in the model. Conclusions: Both location and duration appear to be modifiable correlates of group physical activity level, which may serve to inform intervention efforts to promote physical activity in ASP.
Keywords: Children; Exercise; Accelerometer; Determinants